Rattus nitidus - Thu, Aye Myat; Lwin, Ye Htet; Quan, Rui-Chang (Zenodo, 2024)
109. Rattus nitidus (Hodgson, 1845) Common name: White-footed Indochinese Rat Myanmar name: Distribution: Bhutan, China, India, Nepal, Philippines, Thailand and Vietnam. In Myanmar, recorded in Sagaing Region (Proposed Mahamyaing WS; Thazin Wai et al. 2018) and widely distributed in the mountainous area of the country. Published as part of Thu, Aye Myat, Lwin, Ye Htet & Quan, Rui-Chang, 2024, Mammals of Myanmar: an annotated checklist, pp. 147-197 in Mammalia (Warsaw, Poland) (Warsaw, Poland) 88 (3) on page 163, DOI:10.1515/mammalia-2023-0098, http://zenodo.org/record/13913939